Wedge Factor Dependence on Computer Controlled Wedge System in Siemens ONCOR Linear Accelerator. - Nasir Ilyas; Salman Farrukh; Jawed Iqbal; Syed Abdul Haseeb Ahmad (Journal of Medical Physics and Biophysics, 2016)
Wedge factor is the measurements which shows how much dose reduces to the target after introducing wedge between the source and target. In this work we will obtain the wedge factors by using VW (Virtual wedge) and Physical Wedge (PW) for different field sizes ( 10 x 10 cm2 ,15 x 15 cm2 and 20 x 20 cm2) , wedge angles (15°, 30° ,45° and 60° ) and energies (6 MV and 15 MV). This work will be carried out on Siemen’s linear accelerator (LINAC) and Iba-blue water phantom is used for scanning purpose. CC 13 ionization chamber is used for PW and LDA 99 for VW. The source to surface distance and depth in our work remain 100cm and 10 cm respectively. These detectors will be connected through different electrometers and all the observation will be taken through Omnipro version 7, a dosimetric software. The wedge factors will be plotted against various field sizes for both energies and wedge angles. The mean wedge factor will be analyzed by using Statistics package for social sciences (SPSS, V15) as a function of field size, wedge angle, energy and type of wedge to obtain the significance of these factors .If Analysis of Variance (ANOVA) were performed on the mean wedge factor by using F-test. The observations shows that wedge factor increases with field size and energy in both these conditions this increment is not statically significant , Wedge factor (WF) decreases with wedge angle also not statistically significant. The wedge factor in VW is greater than PW, it is highly statistically significant.